Design Join Composite Memanfaatkan Ketahanan Alam dari Cabang Pohon untuk Meningkatkan Toleransi Kerusakan - Jusef Saiful; Muhammad Yusuf; Sunarko Sunarko (Universitas Islam Raden Rahmat, Malang, 2024)
Optimization and innovation are necessary to enhance the resilience of transportation, particularly through the improvement of connections. Connections play a crucial role, especially in structural designs that often utilize various types of joints. The use of composite connection components inspired by nature, such as tree branch connections, can be a solution to improve joint resilience. Tree branch connections exhibit desired structural properties, including strength, toughness, fatigue resistance, and damage tolerance. The application of Advanced Additive Manufacturing, such as stereo-lithography, is employed to integrate fiber structures in joint designs. These joints aim to replace bolts and nuts, which can damage load-bearing fibers and increase local stresses. Testing indicates that tree branch-inspired joint designs, especially with 37.5% embedding, provide the most optimal results with the best values for stress, displacement, and safety factors compared to other joint design variations.